2017
DOI: 10.1111/febs.13975
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal extension of Mycobacterium tuberculosis Hsp16.3 regulates its oligomerization, subunit exchange dynamics and chaperone function

Abstract: Mycobacterium tuberculosis is a human pathogen that secretes a major immunodominant antigen, namely Hsp16.3, throughout the course of infection. Hsp16.3 belongs to the small heat shock protein family and exhibits a molecular chaperone function that is important for the growth and survival of M. tuberculosis in host cell macrophages. The importance of the N-terminal region for the structure and chaperone function of Hsp16.3 is well understood. However, the effect of the C-terminal region on these properties is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…In the pre-heat treatment assays, it was conjectured that a more favourable secondary structure might aid in improving the chaperone activity of gel-filtered Acr. Our observations indicate that pre-heating the sample might reduce the percentage of β sheets and increase the randomness and disorderliness which corroborates with previous findings (8,10,12). However non-gel-filtered samples did not show any improvement suggesting an analysis of secondary structure that is required to interpret this data.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In the pre-heat treatment assays, it was conjectured that a more favourable secondary structure might aid in improving the chaperone activity of gel-filtered Acr. Our observations indicate that pre-heating the sample might reduce the percentage of β sheets and increase the randomness and disorderliness which corroborates with previous findings (8,10,12). However non-gel-filtered samples did not show any improvement suggesting an analysis of secondary structure that is required to interpret this data.…”
Section: Discussionsupporting
confidence: 91%
“…High levels of purified Acr were obtained after Histag and gel filtration. Earlier studies have shown Acr to be a nonameric 158 kDa in the form of trimer of trimers, 210 kDa and 193 kDa (4,7,8,10). The activity of A samples was two times less than that of B samples at 37°C.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations